Through the lens of identity, a poetic journey of subconscious embodiment in architecture - Gorton, Aidan (School of Architecture, Planning and Geomatics, 2024)
In this paper I will set a foundation around existentialism as a humanism acting as a philosophical base for the analysis. This stems from the isolation described in the preface where my personal experience acted as a catalyst for my interest in better understanding how our relationship with the spaces and environments around us affect our body and mind through time. In better understanding this dialectical relationship between the self and it's surroundings, I will explore the role of architecture as the mediator between humans and the world, and how through the processes and execution of design a poetic experience can be attained. This poetic experience bringing light to our fleeting existence across time. I am going to explore the work of the filmmaker, Akira Kurosawa, as i find his films to have an extraordinary immersive capacity in the poetic experience and often leave me pondering the questions of our existence and relationship with the world, and each other. This exploration of Kurosawa's body of work will provide a framework, from which i believe parallels can be made with architecture, where i will analyse the significance of these principals through their physical manifestation as tactile and intimate architecture.